Physicochemical Characteristics and Storage Stability of Hybrid Beef Patty Using Shiitake Mushroom (Lentinus edodes) - Gyutae Park; Sehyuk Oh; Sanghun Park; Yun-a Kim; Yunhwan Park; Youngjin Kim; Juho Lee; Hwayong Lee; Jungseok Choi (Journal of Food Quality)
This study evaluated the physicochemical characteristics and storage stability (at 0, 3, and 7 days) of hybrid beef patties with different amount of shiitake mushrooms (Lentinus edodes) added. Shiitake mushrooms contain healthy ingredients such as ergosterol and β-glucan. Four proportions of shiitake mushrooms were added to beef patties (T1, 20%, T2, 40%, T3, 60%, T4, 80%) as a substitute for beef and compared with a control group (CON 0%). Chemical composition, water holding capacity (WHC), cooking loss, pH, color, texture profile analysis, and sensory properties of the products were compared on day 0. As a storage stability experiment, volatile basic nitrogen (VBN), 2-thiobarbituric acid reactive substances (TBARS), and total microbial count were compared (0, 3, and 7 days). The results revealed that replacement with shiitake improved the WHC and cooking loss of patties but had a negative effect on sensory properties and storage stability. These results indicate that shiitake mushrooms can be added along with beef to produce hybrid patties; however, the usage amount must be considered.